Permeable material with lightning strike protection and its use in resin infusion processes
By using permeable LSP material in the resin infusion method, the shortcomings of composite parts in lightning strike protection are solved, and the effect of improving manufacturing speed, efficiency and quality is achieved, while providing better lightning strike and electromagnetic compatibility protection.
Patent Information
- Application Number
- CN202080026208.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-03-27
AI Technical Summary
The prior art is difficult to effectively introduce lightning strike protection (LSP) materials when manufacturing composite parts, especially when using resin infusion methods, manual operation is arduous and difficult to ensure surface quality.
A permeable LSP material is used, which consists of a nonwoven veil of randomly arranged fibers, a porous conductive layer and a resin material, which can be used in resin infusion methods, especially in VARTM. The material can be in the form of elongated or continuous strips and is suitable for automatic laying methods such as ATL and AFP to improve manufacturing speed, efficiency and quality.
By introducing permeable LSP materials, the surface quality of the composite structure is improved and protection against lightning strikes, electrostatic discharges and electromagnetic interference is provided, reducing manufacturing costs.
Smart Images

Figure BDA0003286879790000071 
Figure BDA0003286879790000081 
Figure BDA0003286879790000085
Abstract
Description
[0001] The present disclosure generally relates to materials for providing lightning strike protection (LSP) to composite parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0002] Figure 1 A permeable LSP material is presented that may be introduced into a resin infusion process according to one embodiment.
[0003] Figure 2 A permeable LSP material according to another embodiment is shown.
[0004] Figure 3 A permeable LSP material according to yet another embodiment is presented.
[0005] Figure 4 A permeable LSP material according to yet another embodiment is presented.
[0006] Figure 4 A permeable LSP material according to yet another embodiment is presented.
[0007] Figure 5 An exemplary closed mold RTM process is presented.
[0008] Figure 6 An exemplary VARTM method is presented.
[0009] Figure 7 Another exemplary VARTM method is presented.
[0010] Figure 8 is a top view of a permeable LSP structure produced according to one example.
[0011] Fig. 9 A cross-sectional view of a cured composite panel having an embedded LSP material prepared according to one example is shown.
[0012] Fig.10 A cross-sectional view of a cured composite panel having an embedded LSP material prepared according to another example is shown. DETAILED DESCRIPTION
[0013] Fiber-reinforced polymer matrix composites (PMCs) are high-performance structural materials consisting of reinforcing fibers impregnated in a polymer matrix. PMC materials are typically used in applications that require tolerance to aggressive environments, high strength, and / or low weight. Examples of such applications include aircraft parts, such as tails, wings, fuselages, and propellers; automobiles; boat hulls, and bicycle frames.
[0014] Materials used to manufacture aerospace parts such as fuselages and wings must have certain characteristics that protect the parts from damage or hazards caused by common environmental events. Lightning is an example of a common environmental event that can severely damage and / or puncture parts if such parts are not sufficiently conductive and adequately grounded through the aircraft. If lightning strikes a wing component of an aircraft during flight, in addition to causing severe physical damage to the component itself, the event has the potential to cause a dangerous surge current. Surge current is of particular concern because it may eventually come into contact with the fuel reservoir and cause an explosion to occur.
[0015] In order to provide lightning strike protection (LSP) for composite parts made of PMC materials, different methods have been used to enhance the electrical conductivity of the composite parts. The conventional method used in the aerospace industry to impart LSP to composite parts is to introduce metal mesh, screen, mesh metal foil or woven silk fabric into the composite part.
[0016] Such LSP materials can be introduced during the manufacture of composite parts. Composite parts can be manufactured using different methods, one of which is prepreg processing. Prepregs are typically reinforced fiber sheets impregnated with matrix resins (e.g., epoxy-based resins). To form composite parts, prepregs are cut to size and laid on a mold. Metal LSP materials can be introduced between prepreg stacks and outer surface films as a single conductive layer, or by embedding a conductive layer in the surface film. For aerospace applications, such surface films are often introduced into composite parts to improve their surface quality. Surface films are typically epoxy-based films and can be co-cured with prepreg stacks during the manufacture of composite parts. Once in place, the prepreg stacks are enclosed under a vacuum bag together with the conductive layer and the surface film and heat cured under pressure to produce the final composite part. Prepregs to be molded into composite parts have the advantages of easy use and high reliability. However, they also have the following disadvantages: they have limited drapability (i.e., the ability to hang).
[0017] To manufacture composite parts with more complex shapes, resin infusion methods such as resin transfer molding (RTM) and vacuum assisted resin transfer molding (VARTM) have been used. During the RTM method, a dry preform is placed in a closed mold cavity and liquid resin is injected into the cavity under pressure. A dry preform is a molded structure containing dry reinforcing fiber layers and / or fabric plies (which can be held together with a small amount of adhesive). The mold containing the preform is often placed in a vacuum so that the vacuum removes all residual air in the preform and accelerates the RTM method. Once the liquid resin fills the mold cavity, the resin is cured, resulting in the formation of a hardened composite part. VARTM is similar to RTM, except that a single-sided tool is usually used. Typically, VARTM includes: enclosing the preform on the tool surface with a vacuum bag, which is a flexible, fluid-impermeable covering; evacuating between the tool and the bag, thereby causing the bag to compress the preform; and introducing the liquid resin into the evacuated bag through one or more resin supply lines or conduits. Such resin infusion methods are particularly useful in the manufacture of complex shaped structures that are otherwise difficult to manufacture using conventional prepreg techniques.
[0018] Traditionally, dry preforms for forming composite parts via liquid resin infusion are prepared by a manual lamination operation in which superimposed layers of dry fiber material are laid on a tool that substantially defines the shape of the composite part. The fiber material layers may be in the form of non-woven or woven fabrics, such as non-crimp fabrics (NCF), which have not been pre-impregnated with resin. When laying the layers on the tool, the operator must be careful to fit them to the shape of the tool without inducing wrinkling or bulging. In addition, to introduce integrated LSP conductive materials via a resin infusion method, a single conductive layer such as a mesh metal foil is typically placed on the tool surface, the dry preform is then laid, and the entire assembly is then infused with resin. The resin-infused preform is cured together with the metal foil to form a hardened composite part having an LSP metal layer integrated therein. Such manual operations are laborious and slow because the mesh metal foil is a very fragile material that may easily deform and wrinkle, thereby changing the final surface quality.
[0019] It would be desirable to be able to form layups of dry preforms by automated placement processes such as automated tape laying (ATL) and automated fiber placement (AFP), and to be able to introduce LSP materials into such automated processes to increase manufacturing speed, efficiency and quality, and thereby reduce manufacturing costs.
[0020] A permeable LSP material is disclosed herein that can be introduced into a resin infusion process, particularly VARTM. This permeable LSP material can be in the form of an elongated or continuous strip that can be used in automated placement processes such as ATL and AFP. In some embodiments, the LSP material is configured to improve the surface quality of the final composite structure and provide protection against lightning strikes, electrostatic discharge (ESD), and electromagnetic interference (EMI).
[0021] according to Figure 1 In one embodiment shown, the LSP material 10 is a permeable material consisting of at least the following components: (a) a nonwoven veil 11 of randomly arranged fibers; (b) a porous conductive layer 12 having openings extending through its thickness; and (c) a resin material 13 distributed in a non-continuous manner in the nonwoven veil 11 and between the nonwoven veil 11 and the conductive layer 12. The porous conductive layer 12 is adhered to one side of the nonwoven veil 11 because of the presence of the resin material 13 therebetween. The porous conductive layer 12 will face or contact the preform to be infused with resin during the manufacture of the composite part.
[0022] With respect to the resin material, "non-continuous manner" means that the resin material does not form a continuous resin film covering the major surface of the nonwoven veil or the major surface of the conductive layer in a manner that will prevent fluids, liquids or air from flowing through the thickness of the veil or through the thickness of the conductive layer. The resin material is distributed so that the resin-containing nonwoven veil remains porous and most (i.e., more than half) or all of the openings in the conductive layer are not completely blocked. Therefore, liquids, particularly liquid resins, used in RTM and VARTM can flow through the thickness of the LSP material during resin infusion to form a fully embedded LSP solution. In addition, the air initially trapped in the initial dry preform can be evacuated during the degassing process, in which the dry preform is heated to remove any volatiles, moisture trapped in the preform.
[0023] according to Figure 2 In another embodiment shown, the porous conductive layer 12 (as shown in FIG. Figure 1 The non-woven fabric 10 is sandwiched between two non-woven veils 11 and 14, and the resin material 13 is distributed in a non-continuous manner throughout the non-woven veils 11, 14 and on the conductive layer 12. The non-continuous presence of the resin material is as shown in reference Figure 1 Some of the resin material may penetrate through the openings (or perforations) of the conductive layer 12, but the resin material will not completely fill all of the openings. Figure 2 The laminate structure shown in remains a porous and fluid permeable structure through which liquid resin can flow easily. In this embodiment, either of the resin-containing veils (11, 14) will contact a preform to be infused with resin during the manufacture of a composite part.
[0024] exist Figure 1 and Figure 2 In the illustrated embodiment, each nonwoven face yarn (11, 14) without resin material is a thin, lightweight structure having an area weight in the range of 3-50 gsm or 4-15 gsm. "gsm" means g / m 2 Each nonwoven veil may be composed of continuous fibers or chopped fibers made of glass, carbon, or polymers such as thermoplastic polymers. The nonwoven veil may be composed of different types of fibers (ie, fibers of different materials). Thermoplastic fibers are suitable, including fibers made from: polyamides (such as aliphatic polyamides (PA), cycloaliphatic polyamides, aromatic polyamides, polyphthalamides (PPA), ether or ester block polyamides (PEBAX, PEBA)); polyphenylene sulfide (PPS); polyetherimide (PEI); polyimide (PI); polyamidoamide (PAI); polysulfones, including polyarylsulfones (such as polyethersulfone (PES), polyethersulfone-etherethersulfone (PES:PEES), polyetherethersulfone (PEES)); polyaryletherketone (PAEK) (such as polyetherketone (PEK), polyetheretherketone (PEEK)); polyurethanes, including thermoplastic polyurethanes; polycarbonates; polyacetals; polyphenylene oxide (PPO); polyesters; polyethers; polyether nitriles; polybenzimidazoles; liquid crystal polymers (LCP); and combinations and copolymers thereof.
[0025] exist Figure 1 and Figure 2 In the illustrated embodiment, the porous conductive layer 12 (without resin material) can be a mesh metal foil or a metal screen or a metal mesh, preferably having an area weight in the range of about 50 gsm to 850 gsm, or 60 gsm to 350 gsm, or 60 gsm to 195 gsm. The conductive layer can be a perforated metal foil (in sheet form) having perforations throughout its thickness and a thickness in the range of 3 μm to 300 μm. The perforations can have any suitable cross-sectional shape, such as circular or elliptical. Suitable metals can be selected from: copper, aluminum, bronze, titanium, alloys thereof, and combinations thereof. In one embodiment, the porous conductive layer is a perforated copper foil having a thickness in the range of 10 μm-75 μm or an area weight in the range of 60 gsm-350 gsm.
[0026] exist Figure 1 In the illustrated embodiment, the resin material 13 is present in an amount ranging from 20 gsm to 75 gsm or from 25 gsm to 50 gsm. Figure 2 In the illustrated embodiment, the total amount of the resin material in the LSP material is 40 gsm to 150 gsm or 50 gsm to 100 gsm. The resin material is a curable resin containing one or more thermosetting resins. The composition of the resin material will be described in more detail below.
[0027] exist Figure 3 In another embodiment shown, see Figure 1 The LSP material is adhered to a reinforcement textile 15. The reinforcement textile 15 consists of a layer of unidirectional (UD) reinforcement fibers 15a attached to a nonwoven face veil 15b. Figure 3 The UD reinforcing fibers 15a are shown adhered to the perforated conductive layer 12. Alternatively, the veil side 15b of the reinforcing textile 15 can be adhered to the perforated conductive layer 12. The reinforcing textile 15 acts as a stiffening material, which prevents the "accordion pleat" effect during slitting of wide LSP material into narrow width strips or during automated placement of LSP strips. The "accordion pleat" effect refers to the wrinkling and bulging of the strips. The reinforcing textile 15 also functions as the first reinforcement layer during the automated placement method to build the preform. Therefore, the laying of the LSP material and the first reinforcement layer or the last reinforcement layer is carried out in one step instead of in two separate steps, thereby reducing the overall processing time.
[0028] exist Figure 4 In yet another embodiment shown, see Figure 2 The LSP material is adhered to the reinforced textile 15. The reinforced textile 15 is as shown in Figure 3 Again, the UD fibers 15a or the veil 15b may be in contact with the resin-containing veil 13.
[0029] exist Figure 3 and Figure 4 In the illustrated embodiment, the reinforcing textile 15 will contact a preform to be infused with resin during the manufacture of a composite part.
[0030] exist Figure 3 and Figure 4 In the configuration of , the resin material 13 can be replaced by an adhesive that is solid at temperatures up to 50°C and has a softening point at a temperature in the range of 65°C to 125°C as measured by differential scanning calorimetry (DSC). This solid adhesive contains a blend of epoxy resin and thermoplastic polymer, but does not contain any catalyst or crosslinking agent that is active above 65°C. When such a solid adhesive is used, Figure 3 or Figure 4 The amount of adhesive in the LSP multilayer structure shown in may range from 5 gsm to 20 gsm in total.
[0031] See also Figure 1-4The multilayer LSP material can be in the form of a flexible strip, which is lightweight and is configured for an automated placement method, such as ATL or AFP. Due to its flexibility and lightweight properties, such LSP strips can be laid at a significantly faster rate than conventional resin-impregnated prepreg strips. The LSP strip can have a width of about 0.125 inches to about 12 inches (or about 3.17mm to about 305mm). In some embodiments, the LSP strip has a width of about 0.125 inches to about 1.5 inches (or about 3.17mm to about 38.1mm) or about 0.25 inches to about 0.50 inches (or about 6.35mm to about 12.77mm). In other embodiments, the LSP strip can have a width of about 6 inches to about 12 inches (or about 152mm to about 305mm). The length of the strip is continuous or very long relative to its width, for example, at least 10 times its width, and in some cases 100-100,000 times its width. In continuous form, the surface strip may be wound into a roll for storage prior to its application in an automated process.
[0032] ATL and AFP are methods of laying continuous strips onto a mold surface (e.g., a mandrel) using computer-guided robotics to build composite structures or fiber preforms. The ATL / AFP method involves distributing one or more strips side by side on a tool surface to produce a layer of desired width and length, and then building additional layers on the previous layers to provide a stack with desired thickness. Subsequent strips can be oriented at different angles relative to the previous strips. ATL / AFP systems are typically equipped with a robot-controlled head for distributing and compacting direct strips onto a tool surface.
[0033] Resin material
[0034] The resin material in the LSP material of the present disclosure is tacky at room temperature (20°C-25°C), thereby providing the LSP material with a tacky surface on one or both sides thereof. The term "tacky" as used with respect to the resin material means that it is sticky to the touch and can be easily adhered to another surface. The tacky properties of the resin material ensure that the LSP material remains in place when it is placed on a tool surface or laminated to another substrate such as a dry fiber preform without the application of heat. Such tacky properties are advantageous in automated placement methods such as ATL and AFP.
[0035] In various embodiments herein, see in particular Figure 1 and Figure 2The adhesive resin material is formed from a curable resin composition containing one or more thermosetting resins. Examples of suitable thermosetting resins include, but are not limited to, epoxy resins, phenolic resins, cyanate esters, bismaleimides, benzoxazines (including polybenzoxazines), unsaturated polyesters, vinyl ester resins, and combinations thereof.
[0036] In a preferred embodiment, the curable resin composition contains one or more epoxy resins and at least one curing agent. Epoxy resins include monofunctional and multifunctional epoxy resins. Multifunctional epoxy resins (or polyepoxides) contain two or more epoxy functional groups per molecule.
[0037] Examples of suitable multifunctional epoxy resins include polyglycidyl ethers prepared by reacting epichlorohydrin or epibromohydrin with polyphenols in the presence of a base. Suitable polyphenols are, for example, resorcinol, catechol, hydroquinone, bisphenol A (bis(4-hydroxyphenyl)-2,2-propane), bisphenol F (bis(4-hydroxyphenyl)methane), bis(4-hydroxyphenyl)-1,1-isobutane, 4,4'-dihydroxybenzophenone, bis(4-hydroxyphenyl)-1,1-ethane, and 1,5-hydroxynaphthalene.
[0038] Also included are polyglycidyl ethers of polyols. Such polyols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol and trimethylolpropane. Additional epoxy resins include polyglycidyl esters of polycarboxylic acids, such as the reaction products of glycidol or epichlorohydrin with aliphatic or aromatic polycarboxylic acids such as oxalic acid, succinic acid, glutaric acid, terephthalic acid or dimerized fatty acids.
[0039] Other resins may include those derived from the epoxidation products of ethylenically unsaturated alicyclic compounds or from natural oils or fats.
[0040] Also included are liquid epoxy resins which are the reaction product of bisphenol A or bisphenol F with epichlorohydrin. These epoxy resins are liquid at room temperature and generally have an epoxy equivalent weight (g / equivalent) of from about 150 to about 480 as determined by ASTM D-1652.
[0041] Particularly suitable are epoxy novolac resins, which are polyglycidyl derivatives of phenol-formaldehyde novolac or cresol-formaldehyde novolac having the following chemical structure:
[0042]
[0043] Where n = 0 to 5, and R = H or CH3. When R = H, the resin is a phenol novolac resin. When R = CH3, the resin is a cresol novolac resin. The former is used as DEN TM 428、DENTM 431、DEN TM 438、DEN TM 439, and DEN TM 485 is commercially available from Dow Chemical Co. The latter is commercially available from Ciba-Geigy Corp. as ECN 1235, ECN 1273, and ECN 1299. Other suitable novolacs that may be used include SU-8 from Celanese Polymer Specialty Co. In a preferred embodiment, the epoxy novolac resin has a viscosity of 4000-10,000 mPa·s at 25° C. and an epoxy equivalent weight (EEW) of about 190 g / equivalent to about 235 g / equivalent as determined by ASTM D-1652.
[0044] Particularly suitable multifunctional epoxy resins are tetrafunctional aromatic epoxy resins having four epoxy functional groups and at least one glycidylamine group per molecule. An example is the tetraglycidyl ether of methylenedianiline having the following chemical structure:
[0045]
[0046] The amine groups in the structure are shown in the para or 4,4' position of the aromatic ring structure, however, it is understood that other isomers, such as 2,1', 2,3', 2,4', 3,3', 3,4', are possible alternatives. An example of a commercially available tetrafunctional epoxy resin is supplied by Huntsman Advanced Materials. MY 9663, MY9634, MY 9655, MY-721, MY-720, MY-725.
[0047] Another particularly suitable multifunctional epoxy resin is a trifunctional epoxy resin, such as the triglycidyl ether of aminophenol. A specific example of a commercially available trifunctional epoxy resin is supplied by Huntsman Advanced Materials. MY 0510, MY 0500, MY 0600, MY 0610.
[0048] Another suitable trifunctional epoxy resin is a tris-(hydroxyphenyl)-methane based epoxy resin such as supplied by Huntsman Advanced Materials having the following chemical structure 742 resin:
[0049]
[0050] The curable resin composition can be formulated to produce a high T g and high crosslink density. In some embodiments, a combination of one or more epoxy novolac resins and one or more non-phenolic varnish multifunctional epoxy resins (particularly trifunctional and / or tetrafunctional epoxy resins) is used. The relative amounts of epoxy novolac resin and non-phenolic varnish multifunctional epoxy resin can vary, but preferably the amount of epoxy novolac resin is in the range of about 80 to about 100 parts per 100 parts of non-phenolic varnish multifunctional epoxy resin. The combination of epoxy novolac resin and multifunctional epoxy resin in the specified ratio contributes to the desired high T when cured. g and crosslink density.
[0051] Multifunctional epoxy resins can be cured by a variety of latent amine-based curing agents activated at high temperatures (e.g., temperatures above 150°F (65°C)). Examples of suitable curing agents include dicyandiamide (DICY), diaminodiphenyl sulfone (4,4'-DDS or 3,3'-DDS), 4,4'-methylene-bis (3-chloro-2,6-diethylaniline) (MCDEA), guanamine, guanidine, aminoguanidine, and derivatives thereof. Compounds of the class of imidazoles and amine complexes can also be used. In one embodiment, the curing agent is dicyandiamide. In another embodiment, the curing agent is 4,4'-methylene-bis (3-chloro-2,6-diethylaniline) (MCDEA). Amine-based curing agents are present in an amount ranging from about 1% to about 5% by weight based on the total weight of the resin composition.
[0052] A curing accelerator may be used in conjunction with an amine-based curing agent to promote the curing reaction between the epoxy resin and the amine-based curing agent. Suitable curing accelerators may include alkyl and aryl substituted ureas (including aromatic or alicyclic dimethyl ureas) and diureas based on toluenediamine or methylenedianiline. An example of a diurea is 4,4'-methylenebis(phenyl dimethyl urea), U-52 or CA 152 is commercially available from CVC Chemicals and is a suitable accelerator for dicyandiamide. Another example is 2,4-toluene bis(dimethylurea), available as U-24 or CA150 is commercially available from CVC Chemicals, Inc. The curing accelerator may be present in an amount ranging from about 0.5% to about 3% by weight based on the total weight of the resin composition.
[0053] As used herein, the term "cure" or "cure" refers to the irreversible hardening of a prepolymer material or resin or monomer achieved by heating at elevated temperatures, exposure to ultraviolet light and radiation, or chemical additives. The term "curable" means capable of being cured into a hardened material.
[0054] The curable resin composition may further include one or more toughening agents. The toughening agent may be selected from: a thermoplastic polymer; an elastomer; core-shell rubber particles; a pre-reacted adduct as a reaction product of an epoxy resin, a bisphenol and an elastomeric polymer; and combinations thereof. In some embodiments, a combination of two different toughening agents from this group is used. The total amount of one or more toughening agents may be from about 1% to about 30% by weight, in some embodiments from about 10% to about 20% by weight based on the total weight of the resin composition.
[0055] Regarding the pre-reacted adduct, suitable epoxy resins include diglycidyl ether of bisphenol A, diglycidyl ether of tetrabromobisphenol A, hydrogenated diglycidyl ether of bisphenol A, or hydrogenated diglycidyl ether of bisphenol F. Also suitable are alicyclic epoxy resins, which include compounds containing at least one alicyclic group and at least two oxirane rings per molecule. Specific examples include alicyclic alcohols, diepoxides of hydrogenated bisphenol A represented by the following structure:
[0056]
[0057] Examples of such cycloaliphatic epoxy resins are available from CVC Thermoset Specialties 5000 (cycloaliphatic epoxy resin prepared by hydrogenation of bisphenol A diglycidyl ether). Other cycloaliphatic epoxy resins suitable for use in the pre-reacted adduct may include EPONEX TM Cycloaliphatic epoxy resins, such as EPONEX supplied by Momentive Specialty Chemicals TM Resin 1510.
[0058] The bisphenol in the pre-reacted adduct acts as a chain extender for linear or alicyclic epoxy resins. Suitable bisphenols include bisphenol A, tetrabromobisphenol A (TBBA), bisphenol Z, and tetramethylbisphenol A (TMBP-A).
[0059] Suitable elastomers for forming the pre-reacted adduct include, but are not limited to, liquid elastomers such as amine-terminated butadiene acrylonitrile (ATBN), carboxyl-terminated butadiene acrylonitrile (CTBN), and carboxyl-terminated butadiene (CTB). Fluorocarbon elastomers, silicone elastomers, styrene-butadiene polymers are also possible. In an embodiment, the elastomer used in the pre-reacted adduct is ATNB, CTBN, or CTB.
[0060] Suitable thermoplastic toughening agents include polyarylsulfone polymers such as polyethersulfone (PES), polyetherethersulfone (PEES). In some embodiments, the toughening agent is a copolymer of PES and PEES, which is described in US Pat. No. 7,084,213.
[0061] The toughening component may be a core-shell rubber (CSR) particle having a particle size of 300 nm or less. The CSR particles may be any core-shell particle in which a soft core is surrounded by a hard shell. Preferred CSR particles are those having a polybutadiene rubber core or a butadiene-acrylonitrile rubber core and a polyacrylate shell. Commercial sources of CSR particles include Kane Ace TM MX 411 (a suspension of 25% by weight of CSR particles in MY 721 epoxy resin), and Kane Ace TM MX 120 (containing dispersed in DER TM 331 resin, 25% to 37% by weight of CSR particles), and Paraloid from Dow Chemical Company TM EXL-2691 (methacrylate-butadiene-styrene CSR particles having an average particle size of about 200 nm).
[0062] Ceramic microspheres may be added to the curable resin composition. They may be hollow or solid ceramic microspheres. In one embodiment, hollow ceramic microspheres made of an inert silica-alumina ceramic material are used. Microspheres having a diameter in the range of from about 0.1 μm to about 20 μm and preferably from about 1 μm to about 15 μm have been found to be particularly suitable. Examples of commercially available ceramic microspheres particularly suitable for use in the resin film composition of the present invention are available from Zeelan Industries Ltd. under the trade name For example, G-200, G210 and W-200 are sold. These microspheres are hollow silica-alumina spheres with thick walls, no odor and light gray in color. In some embodiments, the amount of ceramic microspheres can be in the range of about 20% to about 40% by weight or about 25% to about 35% by weight based on the total weight of the resin composition. In other embodiments, the amount of ceramic microspheres can be in the range of about 3% to about 15% by weight, or about 5% to about 10% by weight.
[0063] Inorganic fillers in the form of particles (e.g., powders) are added to the resin composition as rheology modifying components to control the flow of the resin composition and prevent agglomeration therein. Suitable inorganic fillers that can be used in the resin film composition include talc, mica, calcium carbonate, aluminum oxide, and fumed silica. In one embodiment, hydrophobic fumed silica (e.g., TS-720) is used as an inorganic filler. The amount of the inorganic filler may be in the range of about 1% to about 5% by weight based on the total weight of the resin composition.
[0064] The curable resin composition may further include one or more optional additives that affect one or more of the mechanical properties, electrical properties, optical properties, and thermal properties of the cured or uncured resin material. Such additives include, but are not limited to, ultraviolet (UV) stabilizers, colorants, and dyes. When such additives are used, their total amount is less than about 5% by weight based on the total weight of the resin composition.
[0065] As an example, discontinuous resin distribution for purposes herein may be effected by film lamination. Figure 1 In an embodiment, the resin material can be applied by: (i) providing an assembly of porous conductive layers, for example, a metal mesh as a top layer, a nonwoven veil as an intermediate layer, and a thin resin film as a bottom layer; (ii) applying heat and pressure to the assembly, for example, by heated rollers, so that the resin film becomes flowable and spreads throughout the veil and on the conductive layer, including the interface between the veil and the conductive layer. Alternatively, the resin film can be an intermediate layer in the assembly in step (i). Due to the small amount of resin used, such lamination does not produce a continuous resin surface on the resulting laminate, and the resulting laminate is porous and permeable to fluids (including liquids and volatiles). For Figure 2 In an embodiment of the present invention, the lamination process is the same, but the assembly includes a porous conductive layer between two nonwoven veils and two outer resin films, each resin film being on the outer surface of each veil).
[0066] Alternatively, a nonwoven veil is placed in contact with a resin film, and then heat is applied to reduce the viscosity of the resin and a vacuum is applied to pull the resin through the veil. The resin spreads throughout the veil but does not form a continuous surface or continuous film on the veil, so that the resulting resin-infused veil remains porous. The porous resin-infused veil is laminated to a porous conductive layer to produce Figure 1 For the configuration shown in Figure 2 A second resin-infused veil prepared in the same manner is laminated to the opposite side of the porous conductive layer.
[0067] As another example, the resin material may be distributed by spraying. The nonwoven veil and porous conductive layer are sprayed separately with the resin solution and then dried to remove the solvent. The resin coated veil and the resin coated conductive layer are then laminated together to produce Figure 1 For Figure 2In a configuration of the present invention, a second resin coated veil prepared in the same manner is laminated to the opposite side of the resin coated conductive layer. Spraying does not produce a continuous resin surface on the veil or the conductive layer. Therefore, the resin coated veil and the resin coated conductive layer remain porous and fluid permeable. Alternatively, only one or more nonwoven veils are coated with the resin solution before laminating one or more veils to the porous conductive layer.
[0068] For spraying, the resin solution can have a solid content of 10%-30% solids. The composition of the resin solution can include one or more thermosetting resins in the form of dispersed solids, at least one curing agent, and a solvent. The one or more thermosetting resins and curing agent are as described above for the resin material. The solvent can be selected from organic solvents such as methyl ethyl ketone (MEK), acetone, dimethylacetamide and N-methylpyrrolidone. Optionally, a thermoplastic polymer can be added to the resin solution as a toughening agent, and the amount of the thermoplastic polymer is up to 10-40 parts per 100 parts of total thermosetting resins (all thermosetting resins combined). The number of parts is measured by weight.
[0069] Solid adhesive
[0070] for Figure 3 and Figure 4 The configuration shown can use a solid adhesive instead of the curable resin material disclosed above. This solid adhesive can be distributed on one or more veils and / or porous conductive layers in a particulate form (e.g., as a powder) and then laminated. The term "particulate form" means in this context in the form of individual particles. The particles can have any shape, such as flakes or other non-spherical shapes. The resulting laminate is then bonded to a reinforced textile layer that itself contains a small amount of adhesive.
[0071] As disclosed above, the adhesive is solid at temperatures up to 50°C, has a softening point at a temperature in the range of 65°C to 125°C as measured by differential scanning calorimetry (DSC), and comprises a blend of an epoxy resin and a thermoplastic polymer, but does not contain any catalyst or crosslinker that is active above 65°C. The epoxy resin may be selected from those disclosed for use in the curable resin composition. The thermoplastic polymer in the epoxy-thermoplastic blend may be a polyarylsulphone polymer soluble in the epoxy resin. Such polyarylsulphone polymers contain ether-linked repeating units and optionally thioether-linked repeating units, wherein the units are selected from:
[0072] —(Ph-A-Ph) n —
[0073] and optionally
[0074] —(Ph) a —
[0075] wherein A is CO or SO2, Ph is phenylene, n=1 to 2 and may be a fraction, a=1 to 4 and may be a fraction, provided that when a exceeds 1, the phenylenes are linearly connected by a single chemical bond or a divalent group other than -CO- or -SO2-, or are fused together directly or through a cyclic portion selected from the group consisting of acid alkyls, (hetero)aromatic compounds, cyclic ketones, cyclic amides, imides, cyclic imides, and combinations thereof.
[0076] The polyaryl sulfone may contain repeating units of —(PhSO2Ph)—, wherein the —(PhSO2Ph)— units are present in the polyaryl sulfone in a ratio such that on average at least two of said units —(PhSO2Ph)— are present sequentially in each polymer chain.
[0077] Preferably, the polyarylsulphone is a copolymer comprising the following units:
[0078] X-Ph-SO2-Ph-X-PhSO2Ph (“PES”) and (I)
[0079] X-(Ph) a -X-PhSO2Ph("PEES") (II)
[0080] wherein X is O or S and is different between units and is 1-4.
[0081] Methods for making this solid adhesive may be found in US Pat. No. 8,927,662 assigned to Cytec Technology Corp., the contents of which are incorporated herein by reference.
[0082] Strengthening textiles
[0083] exist Figure 3 and Figure 4 In an embodiment of the present invention, the reinforcing textile 15 is a dry fluid-permeable material comprising a nonwoven veil bonded to at least one side of a unidirectional (UD) fiber layer, and a small amount of adhesive sufficient to bond the UD fibers to the veil. The total amount of adhesive in the reinforcing textile is about 15% or less by weight based on the total weight of the reinforcing textile, for example, 0.1% to 15% by weight. Based on the total weight of the reinforcing textile, the UD fibers and the nonwoven veil account for more than 80% by weight. The adhesive in the reinforcing textile does not form a continuous film on the nonwoven veil or throughout the UD fibers. Therefore, the reinforcing textile is porous and permeable to the liquid resin to be used in the resin infusion.
[0084] UD fibers are aligned in parallel in the same direction with spacing between adjacent fibers. Suitable UD fibers include glass fibers, carbon (including graphite) fibers, and aramid fibers (eg, Kevlar).
[0085] The nonwoven veil is composed of randomly arranged fibers, which may include thermoplastic fibers or carbon fibers, or a combination of carbon fibers and thermoplastic fibers. The fiber length may vary from 1 / 8 inch (0.32 cm) to 2 inches (5.08 cm). In this embodiment, the area weight of the nonwoven veil is preferably 10 gsm or less, such as 2-10 gsm.
[0086] For nonwoven veils composed of thermoplastic fibers, the fibers can be made of a thermoplastic material selected from the group consisting of polyamides, including aliphatic polyamides, cycloaliphatic polyamides, and aromatic polyamides; polyphthalamides; polyamideimides; polyimides; polyetherimides, polyesters; polyphenylene oxides; polyurethanes; polyacetals; polyolefins; polyarylsulfones, including polyethersulfones, polyetherethersulfones; polyaryletherketones (PAEKs), including polyetheretherketones (PEEKs) and polyetherketoneketones (PEKKs); poly(phenylene sulfides); liquid crystal polymers (LCPs); phenoxys; acrylics; acrylates; mixtures and copolymers thereof. In addition, the nonwoven veil can be composed of two different types of fibers (i.e., fibers having different thermoplastic compositions).
[0087] Suitable binders for reinforcing textiles include: polyurethanes, which are non-crosslinked, partially or fully crosslinked, or modified polyurethane polymers; partially or fully crosslinked copolymers of polyhydroxy ethers and polyurethanes; epoxy resins, which are non-crosslinked, partially or fully crosslinked, or modified epoxy resins; poly(hydroxy ether) resins, which are non-crosslinked, partially or fully crosslinked.
[0088] The adhesive used to strengthen the textile can also be the same as that described above. Figure 3 and Figure 4 The configuration disclosed herein is the same as the solid adhesive composed of epoxy resin and thermoplastic polymer.
[0089] In one embodiment, the adhesive is an aqueous dispersion comprising: (i) a copolymer of a polyhydroxy ether and a polyurethane, (ii) a crosslinker; and optionally, (iii) a catalyst. The crosslinker may be an aminoplast crosslinker, for example, an aminoplast crosslinker of the methoxyalkyl melamine class. The catalyst may include, but is not limited to, a proton donor acid such as a carboxylic acid, phosphoric acid, an alkyl acid phosphate, a sulfonic acid, a disulfonic acid; and / or a Lewis acid such as aluminum chloride, aluminum bromide or aluminum iodide, an iron halide, a boron trihalide; and many other substances in these two classes as are well known to those skilled in the art.
[0090] An exemplary method for applying an adhesive includes: applying an adhesive in particulate form or liquid form to a stretched UD fiber layer and / or a nonwoven veil; and bonding the nonwoven veil to at least one side of the fiber layer. In another exemplary method, an adhesive is added during the manufacture of the nonwoven veil. The resulting adhesive-containing veil is then bonded to the UD fiber layer.
[0091] According to one embodiment, a method for making a reinforced textile includes: applying a first adhesive in the form of a powder to a dry fiber web of stretched UD fibers (e.g., carbon fibers) and / or a nonwoven veil (e.g., composed of carbon fibers and / or thermoplastic fibers); bonding the nonwoven veil to at least one side of the fiber web to form a laminate; applying a second adhesive in the form of a liquid composition to the laminate, for example by dip coating; and drying the adhesive-treated laminate in an oven.
[0092] Application in resin infusion method
[0093] The LSP material disclosed herein is configured for use in resin infusion processes such as RTM and VARTM. Typically, the LSP material is applied to the outer surface of a fiber preform in the shape of a composite part, and the combined components are infused with resin. After the resin infused preform is cured to form a hardened composite structure, the LSP material becomes an integrated part of the cured structure.
[0094] for Figure 1 The LSP material shown is placed on the preform to be resin infused so that the resin-containing veil 11 is the outermost layer before resin infusion. Figure 2 The LSP material shown can be placed in contact with either of the resin-containing veils (11 or 14) in the preform to be infused with resin. Figure 3 and Figure 4 The LSP material is shown with the reinforcing textile 15 in contact with the preform to be infused with resin.
[0095] The preform disclosed herein is composed of a stack of components or multiple dry reinforcing fiber layers. The reinforcing fiber layer in the preform can be any type of textile known in the prior art for making composite materials. Examples of suitable fabric types or configurations include, but are not limited to: all woven fabrics include plain weaves, twill weaves, satin weaves, spiral weaves, and single weaves (uni-weave); all multi-axial fabrics, examples of which include warp knitted fabrics and non-crimped fabrics (NCF); knitted fabrics; woven fabrics; all non-woven fabrics, examples of which include non-woven mats and felts composed of short-cut and / or continuous fiber filaments; and combinations of the above-mentioned fabric types. For some applications, the preform may contain a porous foam core or a honeycomb core between two stacks of fiber layers.
[0096] The reinforcing fibers for the preform may be made from a material selected from, but not limited to, glass (including electrical glass or E-glass), carbon (including graphite), aramid, polyamide, high modulus polyethylene (PE), polyester, poly-p-phenylene-benzoxazole (PBO), boron, quartz, basalt, ceramics, and combinations thereof.
[0097] The preform can be prepared by an automated placement process such as ATL or AFP, in which multiple fiber strips are laid side by side to form a fiber layer of the desired size, and subsequent layers are laid in the same manner to build up a stack of the desired thickness. The LSP material of the present disclosure can be introduced into such an automated placement process to form the first layer on the tool surface before laying down the fiber layer, or as the last layer after the preform stack has been formed.
[0098] Figure 5 An exemplary closed mold RTM process is shown in which an assembly of a dry fiber preform 50 (a stack of fiber layers) and LSP material 51 is placed in a closed mold cavity 52 of a molding tool, and liquid resin is then injected into the cavity under pressure. The mold cavity 52 is defined by two or more die parts, such as Figure 5 The upper die head part 52a and the lower die head part 52b are shown in FIG. At least one of the die head parts contains a temperature control mechanism to regulate the temperature of the molding tool. The mold cavity 52 is in fluid communication with a resin injection pipeline (not shown) and is connected to a vacuum source via a vacuum pipeline (not shown). The resin injection pipeline and the vacuum pipeline are arranged in such a way that the resin flows through the LSP material 51 and flows through the thickness of the preform 50. The LSP material 51 is based on Figure 1-4 Any of the embodiments shown. During operation, the molding tool is clamped closed, heated and evacuated, and then liquid resin is injected into the mold cavity 52 through the resin line under pressure. Once the resin infusion of the preform is completed, the mold cavity is heated while maintaining high pressure to cure the resin-infused preform, thereby forming a cured and hardened composite structure with integrated LSP material. After curing, the molding tool is opened and the cured composite structure is removed from the molding tool.
[0099] Figure 6An exemplary VARTM method is shown in which an assembly of a fiber preform 60 and an LSP material 61 is enclosed between a single-sided molding tool 62 and a flexible, gas-impermeable sheet or "vacuum bag" 63. The vacuum bag 63 is sealed to the tool 62 by a sealing element 64. The enclosed vacuum bag is connected to a resin supply line (not shown, which may contain a series of conduits) and a vacuum line (not shown). A resin distribution net 65 is placed between the preform 60 and the tool 62 and is in contact with the resin supply line to enhance the distribution of the resin in the preform. In an alternative embodiment, the LSP material 61 is in contact with the resin distribution net 65 instead of the preform 60.
[0100] During the VARTM operation, a relative vacuum is drawn between the tool 62 and the vacuum bag 63, causing the bag to compress the LSP material / preform assembly. Liquid resin is introduced into the evacuated bag through a resin supply line. A number of independent resin supply lines may be used to facilitate complete wetting or infusion of the liquid resin throughout the preform. The vacuum line and one or more resin supply lines are strategically positioned relative to each other in a manner that enables resin infusion to penetrate the thickness of the LSP material / preform assembly to saturate the entire assembly. In this regard, a vacuum source may be applied on one side of the assembly and resin introduced on the opposite side, such as Figure 6 shown.
[0101] Figure 7 Another exemplary VARTM method is shown, in which the assembly of a preform 70 and an LSP material 71 is enclosed between a molding tool 72 and a flexible gas permeable film 73. The gas permeable film 73 contains micropores throughout and is gas permeable but liquid resin impermeable. The gas permeable film 73 is enclosed by an external gas impermeable cover or vacuum bag 74. A sealing element 76 is provided to seal each of the gas permeable film 73 and the vacuum bag 74 to the tool 72. A resin distribution mesh 75 is placed between the preform 70 and the tool 72 and is in contact with a resin supply line to enhance the distribution of resin in the preform 70. In an alternative embodiment, the LSP material 71 is in contact with the resin distribution mesh 75 instead of the preform 70. A vacuum source is connected to the space between the gas permeable film 73 and the vacuum bag 74.
[0102] In operation, vacuum is drawn from the space between the vacuum bag 74 and the tool 72, causing the bag to compress the LSP material / preform assembly. Liquid resin is introduced into the LSP material / preform assembly via the resin supply line and with the help of the resin distribution mesh 75. Due to the vacuum pressure, the resin is pulled through the thickness of the LSP material / preform assembly, but the gas permeable membrane 73 prevents the resin from flowing into the space between the gas permeable membrane 73 and the vacuum bag 74.
[0103] Should understand Figure 5-7 It is merely demonstrated how the LSP material of the present disclosure may be used in a resin infusion process. The use of the LSP material disclosed herein is not limited to any specific arrangement of RTM or VARTM.
[0104] Examples
[0105] Example 1
[0106] Figure 8 is a top view image (magnification of x50) showing a permeable LSP structure formed by laminating a 10gsm nonwoven glass veil and a 26gsm epoxy-based resin film under vacuum and heat in a first stage, and then laminating the resin infused veil to a 73gsm mesh copper foil (or copper screen) under vacuum and heat.
[0107] Example 2
[0108] The permeable LSP material is formed by combining 195gsm open mesh copper foil (ECF), two glass veils (10gsm each), and two epoxy-based SM905C films (50gsm each) so that the ECF is sandwiched between the two glass veils and the epoxy-based film is the outermost layer, followed by lamination of the assembly under vacuum and heat. A dry preform is formed by laying 16 NCF fabric plies (268gsm each), which are arranged in a quasi-isotropic symmetrical stack. The LSP material is placed on the dry preform and the entire assembly is infused with an epoxy-based resin composition at 90°C in a VaRTM device. The preform is fully infused within 3min and about 136g of resin is used. The resin-infused preform is cured at 180°C for 120min to form a hardened composite panel.
[0109] Fig. 9 A cross section of a cured composite panel with embedded LSP material is shown.
[0110] Example 3
[0111] A permeable LSP material was formed as described in Example 2, except that 73 gsm ECF was used. The LSP material was placed on a dry preform consisting of 16 NCF plies (268 gsm per ply) and the entire assembly was infused with an epoxy-based resin composition in a VaRTM apparatus at 90°C. The preform was fully infused within 3 min and about 134 g of resin was used. The resin infused preform was cured at 180°C for 120 min to form a hardened composite panel.
[0112] Fig.10A cross section of a cured composite panel with embedded LSP material is shown.
Claims
1. A permeable material, the permeable material being porous and fluid permeable, the permeable material comprising: a first nonwoven veil comprising randomly arranged fibers; b a porous conductive layer having openings extending through its thickness; as well as c a resin material distributed in a non-continuous manner throughout the first nonwoven veil and between the first nonwoven veil and the conductive layer such that the first nonwoven veil remains porous and more than half or all of the openings in the conductive layer are not blocked by the resin material, wherein the porous conductive layer comprises two opposing surfaces and the first nonwoven face veil is adhered to one of the opposing surfaces, and The resin material comprises one or more thermosetting resins and a curing agent.
2. The permeable material of claim 1, further comprising: d a second nonwoven veil comprising randomly arranged fibers, wherein the second nonwoven face yarn is adhered to the other of the opposing surfaces of the porous conductive layer, and the resin material is distributed in the second nonwoven face yarn in a non-continuous manner such that the second nonwoven face yarn maintains porosity.
3. The permeable material of claim 1, further comprising: A reinforced textile comprising a second nonwoven face veil bonded to a unidirectional fiber layer, wherein the second nonwoven face veil or the unidirectional fiber layer is adhered to the other of the opposing surfaces of the porous conductive layer, and wherein the reinforced textile is porous and fluid permeable.
4. The permeable material of claim 2, further comprising: A reinforced textile comprising a third nonwoven face veil bonded to a unidirectional fiber layer, wherein the third nonwoven face veil or the unidirectional fiber layer is adhered to the second nonwoven face veil, and wherein the reinforced textile is porous and fluid permeable.
5. The permeable material of claim 1, wherein: The resin material is present in an amount ranging from 20 gsm to 75 gsm.
6. The permeable material of claim 1, wherein: The resin material is present in an amount ranging from 25 gsm to 50 gsm.
7. The permeable material of claim 2, wherein: The resin material is present in an amount ranging from 40 gsm to 150 gsm.
8. The permeable material of claim 2, wherein: The resin material is present in an amount ranging from 50 gsm to 100 gsm.
9. The permeable material according to any one of claims 1 to 8, wherein The resin material comprises one or more multifunctional epoxy resins and an amine compound as a curing agent, and optionally a toughening agent, wherein the toughening agent is selected from the group consisting of: a thermoplastic polymer; an elastomer and a combination thereof.
10. The permeable material of claim 9, wherein: The elastomer is selected from core-shell rubber particles.
11. A permeable material, the permeable material being porous and fluid permeable, the permeable material comprising: a first nonwoven veil comprising randomly arranged fibers; b a porous conductive layer having openings extending through its thickness; as well as c an adhesive distributed in a non-continuous manner throughout the first nonwoven veil and between the first nonwoven veil and the conductive layer such that the first nonwoven veil remains porous and more than half or all of the openings in the conductive layer are not blocked by the adhesive; d a reinforced textile comprising a second nonwoven face veil bonded to a unidirectional fiber layer, wherein the conductive layer is sandwiched between the first nonwoven face yarn and the reinforcing textile, and The adhesive comprises a blend of an epoxy resin and a thermoplastic polymer but does not contain any catalyst or cross-linking agent that is active above 65°C.
12. A permeable material, the permeable material being porous and fluid permeable, the permeable material comprising: a first nonwoven veil and a second nonwoven veil, each comprising randomly arranged fibers; b a porous conductive layer having openings extending through its thickness; as well as c an adhesive distributed in a non-continuous manner throughout the first and second nonwoven veils and between each nonwoven veil and the conductive layer such that the first and second nonwoven veils remain porous and more than half or all of the openings in the conductive layer are not blocked by the adhesive; d A reinforced textile comprising a third nonwoven face veil bonded to a unidirectional fiber layer, wherein the conductive layer is sandwiched between the first nonwoven face yarn and a second nonwoven face yarn, and the reinforcing textile is adhered to the second nonwoven face yarn, wherein the adhesive comprises a blend of an epoxy resin and a thermoplastic polymer but does not contain any catalyst or crosslinking agent active above 65°C, and Wherein the reinforced textile is porous and fluid permeable.
13. A permeable material as claimed in claim 11 or 12, wherein: The adhesive comprises a blend of an epoxy resin and a polyarylsulphone polymer.
14. The permeable material of claim 11 or 12, wherein: The adhesive comprises polyethersulfone and a copolymer of polyetherethersulfone.
15. The permeable material of claim 11 or 12, wherein: The adhesive is present in a total amount of 5 gsm to 20 gsm.
16. The permeable material of claim 11 or 12, wherein: The first nonwoven face veil has an area weight in the range of 3 gsm to 50 gsm.
17. The permeable material of any one of claims 2, 4, 7 and 12, wherein: The second nonwoven face veil has an area weight in the range of 3 gsm to 50 gsm.
18. The permeable material of claim 1, 11 or 12, wherein: The first nonwoven face veil comprises fibers formed from glass, carbon, or one or more polymers.
19. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer is a metal mesh.
20. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer is a metal mesh.
21. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer is a perforated metal foil.
22. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer has an area weight in a range of 50 gsm to 850 gsm.
23. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer comprises a metal selected from the group consisting of copper, aluminum, titanium, alloys, and combinations thereof.
24. The permeable material of claim 1, 11 or 12, wherein: The porous conductive layer comprises a metal selected from bronze.
25. The permeable material of any one of claims 3, 4, 11 and 12, wherein: The nonwoven veil in the reinforcing textile comprises carbon fibers or thermoplastic fibers, or a mixture of carbon fibers and thermoplastic fibers, and the unidirectional fibers in the reinforcing textile are carbon fibers.
26. The permeable material of claim 1, 11 or 12, wherein: The permeable material is in the form of a continuous strip having a width in the range of 0.125 inches to 12 inches and a length at least 10 times its width.
27. The permeable material of claim 26, wherein: The strip has a length that is at least 100 times its width.
28. A preform configured to receive liquid resin by resin infusion, the preform comprising: a preform comprising a plurality of reinforcing fiber layers, each reinforcing fiber layer being porous and fluid permeable; as well as A permeable material as claimed in any one of claims 1 to 27 in contact with the outer surface of the preform.
29. A method for forming a composite part, the method comprising: Infusing liquid resin into the preform as claimed in claim 28; as well as The resin infused preform is cured.
30. A method for forming the permeable material of claim 1, the method comprising: (i) combining a nonwoven veil, a porous conductive layer having openings extending through its thickness, and a resin film to form an assembly, wherein the resin film or the conductive layer is in the middle of the assembly; (ii) applying heat and pressure to the assembly so that the resin film becomes a flowable resin that spreads throughout the nonwoven veil but does not form a continuous resin film and does not block the openings in the porous conductive layer.
31. A method for forming a permeable material as claimed in claim 2, the method comprising: a combining two nonwoven veils, two resin films and a porous conductive layer having openings extending through its thickness to form an assembly, wherein the conductive layer is between the two nonwoven veils and the two resin films are the outermost layers; b. Applying heat and pressure to the assembly so that the resin film becomes a flowable resin that spreads throughout the nonwoven veil but does not form a continuous resin film and does not block the openings in the porous conductive layer.
32. A method for forming the permeable material of claim 1, the method comprising: (i) placing a resin film in contact with a nonwoven face veil; (ii) applying heat to the resin film to reduce the viscosity of the resin to produce a flowable resin; (iii) applying a vacuum to draw the flowable resin through the nonwoven veil, thereby causing the resin to spread throughout the nonwoven veil without forming a continuous resin surface on the nonwoven veil, wherein the resulting resin-containing nonwoven veil retains porosity after heating and vacuuming; and (iv) laminating the resin-containing nonwoven veil to a porous conductive layer having openings extending through its thickness, wherein the conductive layer retains its porosity after lamination.
33. A method for forming the permeable material of claim 1, the method comprising: (i) spraying a resin solution onto a first nonwoven veil and separately onto a porous conductive layer to form a porous first resin-coated veil and a porous first resin-coated conductive layer; (ii) drying the first resin-coated nonwoven veil and the first resin-coated conductive layer, and (iii) laminating the first resin-coated nonwoven veil to one side of the resin-coated conductive layer, wherein the resin solution comprises one or more thermosetting resins, a curing agent, a thermoplastic polymer optionally as a toughening agent, and a solvent in an amount sufficient to produce a solution having a solids content of 10% to 30% solids, and wherein the first nonwoven veil and the conductive layer maintain porosity after being sprayed with the resin solution.
34. A method for forming the permeable material of claim 2, the method comprising: (i) spraying a resin solution onto a first nonwoven veil and separately onto a porous conductive layer to form a porous first resin-coated veil and a porous first resin-coated conductive layer; (ii) drying the first resin-coated nonwoven veil and the first resin-coated conductive layer, and (iii) laminating the first resin-coated nonwoven veil to one side of the resin-coated conductive layer, wherein the resin solution comprises one or more thermosetting resins, a curing agent, a thermoplastic polymer optionally as a toughening agent, and a solvent in an amount sufficient to produce a solution having a solids content of 10% to 30% solids, and wherein the first nonwoven veil and the conductive layer retain porosity after being sprayed with the resin solution; and The method further comprises: spraying the resin solution onto a second nonwoven veil to form a second resin-coated nonwoven veil; drying the second resin-coated nonwoven veil; and laminating the second resin-coated nonwoven veil to an opposite side of the resin-coated conductive layer, wherein the second nonwoven veil maintains porosity after being sprayed with the resin solution.
35. A method for forming the permeable material of claim 1, the method comprising: (i) spraying a resin solution onto a first nonwoven veil to form a resin-coated veil; (ii) drying the resin coated veil; as well as (iii) laminating the resin coated veil to a porous conductive layer having openings extending through its thickness, wherein the resin solution comprises one or more thermosetting resins, a curing agent, a thermoplastic polymer optionally as a toughening agent, and a solvent in an amount sufficient to produce a solution having a solids content of 10% to 30% solids, and wherein the first nonwoven veil retains porosity after being sprayed with the resin solution.
36. The method of any one of claims 33 to 35, wherein: The resin solution contains one or more epoxy resins, an amine compound as a curing agent, and a thermoplastic polymer in an amount of 10 to 40 parts by weight per 100 parts by weight of the epoxy resin.
37. A method for forming the permeable material of claim 3, the method comprising: (i) distributing an adhesive in the form of particles or powder on a first nonwoven veil to form a first adhesive-containing nonwoven veil; (ii) laminating the first binder-containing nonwoven veil to one side of a porous conductive layer having openings extending through its thickness; (iii) laminating a reinforcing textile to an opposite side of a porous conductive layer having openings extending through its thickness, wherein the reinforced textile comprises a second nonwoven face yarn bonded to a unidirectional fiber layer, and in step (iii) the second nonwoven face yarn or the unidirectional fiber layer is adjacent to the conductive layer during lamination.
38. A method for forming the permeable material of claim 4, the method comprising: (i) distributing an adhesive in the form of particles or powder on a first nonwoven veil and a second nonwoven veil to form a first adhesive-containing nonwoven veil and a second adhesive-containing nonwoven veil; (ii) laminating the first binder-containing nonwoven veil to one side of a porous conductive layer having openings extending through its thickness; (iv) laminating the second binder-containing nonwoven veil to an opposite side of the porous conductive layer; and (v) laminating a reinforcement textile to the second binder-containing nonwoven veil; wherein the reinforced textile comprises a third nonwoven face yarn bonded to a unidirectional fiber layer, and in step (v) the third nonwoven face yarn or the unidirectional fiber layer is adjacent to the binder-containing second nonwoven face yarn during lamination.
Citation Information
Patent Citations
Compositions adapted for chain linking
US7084213B2
Binder of reactive polyarylethersulphone and epoxy resin
US8927662B2
Improvements in or relating to electrically conducting materials
CN108430747A